What is the standard form of y= (x-x^2)(x-8) -(x+3)^3y=(x−x2)(x−8)−(x+3)3? Algebra Polynomials and Factoring Polynomials in Standard Form 1 Answer Barney V. Feb 1, 2018 y=-2x^3-35x-27y=−2x3−35x−27 Explanation: y=(x-x^2)(x-8)-(x+3)^3y=(x−x2)(x−8)−(x+3)3 :.y=(x-x^2)(x-8)-(x+3)(x+3)(x+3) :.y=-x^3+9x^2-8x-(x^3+9x^2+27x+27) :.y=-x^3+9x^2-8x-x^3-9x^2-27x-27 :.y=-2x^3-35x-27 Answer link Related questions What is a Polynomial? How do you rewrite a polynomial in standard form? How do you determine the degree of a polynomial? What is a coefficient of a term? Is x^2+3x^{\frac{1}{2}} a polynomial? How do you express -16+5f^8-7f^3 in standard form? What is the degree of 16x^2y^3-3xy^5-2x^3y^2+2xy-7x^2y^3+2x^3y^2? What is the degree of the polynomial x^4-3x^3y^2+8x-12? What is the difference between a monomial, binomial and polynomial? How do you write y = 2/3x + 5 in standard form? See all questions in Polynomials in Standard Form Impact of this question 1386 views around the world You can reuse this answer Creative Commons License